2005
DOI: 10.1210/en.2004-1093
|View full text |Cite
|
Sign up to set email alerts
|

Central Infusion of Agouti-Related Peptide Suppresses Pulsatile Luteinizing Hormone Release in the Ovariectomized Rhesus Monkey

Abstract: Agouti-related peptide (AGRP), an endogenous melanocortin receptor antagonist, is a powerful orexigenic peptide when infused centrally. AGRP and neuropeptide Y (NPY), another orexigenic peptide, are colocated within the same neurons in the arcuate nucleus. Both NPY and AGRP mRNA expression increases during food restriction, a condition that is known to suppress the GnRH pulse generator and reproductive function. Although NPY has been shown previously to suppress LH secretion in the ovariectomized monkey, data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 50 publications
3
41
1
4
Order By: Relevance
“…Deficiency of either NPY or its receptors recovered fertility [92]. It has been reported that AgRP has an inhibitory effect on LH secretion in ovariectomized monkeys [161]. In this sense, ablation of AgRP expressing neurons in ob/ob mice recovered fertility [169].…”
Section: Npymentioning
confidence: 89%
“…Deficiency of either NPY or its receptors recovered fertility [92]. It has been reported that AgRP has an inhibitory effect on LH secretion in ovariectomized monkeys [161]. In this sense, ablation of AgRP expressing neurons in ob/ob mice recovered fertility [169].…”
Section: Npymentioning
confidence: 89%
“…The orexigenic peptides AGRP and NPY are both potent inhibitors of pulsatile LH secretion [61,62]. AGRP is an endogenous antagonist of Mc3/4r.…”
Section: Discussionmentioning
confidence: 99%
“…As both NPY-knockout mice and AgRP-deficient mice were shown to exhibit improved reproductive phenotypes in response to nutritional stress (fasting and LepR deficiency, respectively), it appears that they are both independently involved in the suppression of GNRH. These data highlight both the powerful inhibitory tone NPY/AgRP-expressing neurons exert on reproductive function and also reveal that leptin signaling exclusively in NPY/AgRP neurons is sufficient to permit fertility (Vulliemoz et al 2005).…”
Section: Npy/agrp-expressing Neuronsmentioning
confidence: 71%
“…A subset of GABAergic neurons in the arcuate nucleus (ARC) of the hypothalamus co-express neuropeptide Y (NPY) and agouti-related peptide (AgRP), which are both orexigenic neuropeptides shown to have predominantly inhibitory effects on GNRH neurons (McShane et al 1992, Cone 2005, Vulliemoz et al 2005, Roa & Herbison 2012. NPY/AgRP neurons, in turn, are directly modulated by insulin (Konner et al 2007) and leptin (Elias et al 1999) and are also innervated by ghrelin-expressing neurons (Cowley et al 2003).…”
Section: Npy/agrp-expressing Neuronsmentioning
confidence: 99%